Cervical Spondylosis: Innovative Techniques for Physical Therapy-An Updated Review - Al-Mutairi, Atef Mohammed Faleg; Almutairi, Sanad Thawabe Falag; Alruaidan, Abdulaziz Raad; Almutairi, Dhay Mudlah; Alqthami, Abdullah Mutlaq Ghazi (Journal of Ecohumanism, 2024)
Cervical spondylosis is a degenerative disorder of the cervical spine affecting intervertebral discs, facet joints, and ligaments. It is commonly seen in individuals over 50 years old and presents with neck pain, stiffness, and potential neurological symptoms. The condition significantly impacts quality of life and contributes to increased healthcare costs and disability rates. Aim: This review explores innovative physical therapy techniques for managing cervical spondylosis, aiming to enhance symptom relief and functional recovery. Methods: A systematic review of recent literature was conducted to identify non-invasive, evidence-based physical therapy interventions. The review included randomized controlled trials, cohort studies, and meta-analyses published in peer-reviewed journals. The primary focus was on therapeutic exercises, manual therapy, neuromuscular re-education, and technology-assisted rehabilitation methods. Results: Innovative techniques such as cervical proprioceptive training, deep tissue mobilization, and neuromuscular electrical stimulation demonstrated significant improvements in pain reduction and functional mobility. Studies also highlighted the benefits of virtual reality-based rehabilitation and biomechanical feedback interventions in enhancing patient adherence and outcomes. Traditional methods, including cervical traction and postural correction exercises, remained effective but showed greater efficacy when combined with newer therapeutic approaches. Conclusion: Physical therapy plays a crucial role in managing cervical spondylosis. Combining traditional methods with innovative techniques leads to better pain control, improved mobility, and enhanced patient engagement. The integration of technology-based rehabilitation strategies may further optimize treatment outcomes. Future research should focus on long-term efficacy and cost-effectiveness of these approaches.